The Impact of Changes in World Oil Prices, Interest Rates, and Net Exports on The Exchange Rate of ASEAN-4 Countries - Palupi, Dyah Ayu; Purwono, Rudi (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2024)
This research examines the impact of changes in world oil prices, interest rates, and net exports on exchange rates in four ASEAN countries (Indonesia, Malaysia, Thailand, and the Philippines). The method used is the Panel Vector Error Correction Model (PVECM) over 2000Q1-2020Q4. The variables analyzed include exchange rates, world oil prices, interest rates, and net exports. The research findings indicate that (1) world oil prices affect exchange rates in both the short and long term, with exchange rates appreciating in the initial period and depreciating after the third period due to oil price shocks; (2) interest rates influence both the short and long term, with exchange rates tending to appreciate in response to interest rate shocks; and (3) net exports only affect the exchange rates in the long term, with exchange rates tending to depreciate in response to net export shocks.